Pengaruh Irama Sirkadian Terhadap Memori Jangka Pendek pada Mahasiswa Fakultas Kedokteran Universitas Mulawarman: The Effect of Circadian Rhythm on Short-Term Memory in Medical Study of the Medical Faculty of Mulawarman University - Muhammad Fachrian Akbar; Agustina Rahayu Magdaleni; Hary Nugroho; Endang Sawitri; Arie Ibrahim (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
ABSTRACT Short-term memory is a form of cognitive function to store information in a short time, which is important to support daily work and learning activities. Circadian rhythm is a physical, mental, and behavioral changes that occurs in 24-hour daily cycle which is believed to be a factor that affecting short term memory , for example sleep-wake cycle. This study was aimed to determine the effect of routinity of aerobic on short-term memory in students at the Faculty of Medicine, University of Mulawarman. This analytic observational study with cross-sectional method used 94 male respondents at the Faculty of Medicine, Mulawarman University, consisting of the Medical Study Program, Dentistry Study Program, and Nursing with stratified random sampling technique. The research results showed the most circadian rhythm type is night chronotype as many as 71 people (76%) (p=0.031). Short-term memory scores were obtained by 41 people (44%) on good category and 53 people (56%) on bad category. It was concluded that there is an effect of circadian rhythm on short-term memory in Medical Study of The Medical Faculty of Mulawarman University. Keyword : Circadian rhythm, Short-term memory, Medical student, Scenery Picture Memory Test (SPMT) ABSTRAK Memori jangka pendek merupakan bentuk fungsi kognitif untuk menyimpan informasi yang tersedia dalam waktu yang singkat dimana hal ini penting untuk menunjang aktivitas pekerjaan maupun pembelajaran sehari-hari. Irama sirkadian adalah suatu perubahan fisik, mental, dan perilaku yang tejadi mengikuti siklus harian 24 jam yang diyakini sebagai faktor yang mempengaruhi memori jangka pendek, contohnya seperti siklus bangun tidur. Penelitian ini bertujuan untuk mengetahui pengaruh aerobik rutin terhadap memori jangka pendek pada mahasiswa di Fakultas Kedokteran Universitas Mulawarman. Penelitian observasional analitik dengan metode potong lintang ini menggunakan 94 responden laki-laki di Fakultas Kedokteran Universitas Mulawarman yang terdiri atas Program Studi Kedokteran, Program Studi Kedokteran Gigi, dan D3 Keperawatan dengan menggunakan teknik stratified random sampling. Hasil penelitian menunjukan tipe irama sirkadian terbanyak ialah kronotipe malam yaitu 71 orang (76%) dengan nilai p = 0,031. Nilai memori jangka pendek didapatkan 41 orang (44%) dalam kategori baik dan 53 orang (56%) kategori tidak baik. Disimpulkan bahwa terdapat pengaruh irama sirkadian terhadap memori jangka pendek pada Mahasiswa Fakultas Kedokteran Universitas Mulawarman. Kata Kunci : Irama sirkadian, Memori jangka pendek, Mahasiswa kedokteran, Scenery Picture Memory Test (SPMT)